South African Teachers' Insights on Improving the Sensory Classroom Teacher Questionnaire (SCTQ) for Inclusive Education and ADHD Support - Hannelie Du Preez (MDPI AG, 2024)
The Sensory Classroom Teacher Questionnaire (SCTQ) is a psycho-educational tool designed to empower teachers in creating sensory-rich, inclusive environments that promote diversity, equity, accessibility, and inclusivity through the application of sensory ergonomics. Unlike other tools that focus on isolated strategies, the SCTQ takes a holistic approach by optimizing the overall classroom environment to meet the sensory and ergonomic needs of learners, particularly those with ADHD and sensory integration/processing challenges. This makes the SCTQ especially vital in diverse and under-resourced quintile schools, where creating sensory-optimized, inclusive environments is essential for fostering equitable learning experiences. By addressing sensory needs through thoughtful classroom design, the SCTQ not only strengthens learners' cognitive development and socio-emotional well-being but also improves behavior regulation, physical comfort, and overall functioning. This manuscript is part of a larger exploratory mixed-methods study that validated the SCTQ using both qualitative and quantitative approaches. Here, the focus is on the qualitative aspect, utilizing thematic analysis to explore data from 23 focus group interviews with 88 Grade 1, 2, and 3 teachers from various Quintile 1-5 schools in Gauteng, South Africa. Guided by the enactivism paradigm, the study emphasizes the crucial role teachers play in creating and adapting sensory environments. Their insights were key to refining the SCTQ, ensuring it is practical, developmentally appropriate, culturally, linguistically, contextually, and socio-economically relevant. Developed through collaboration among researchers, specialists, and teachers, the SCTQ supports sensory ergonomic practices, raises awareness of ADHD and sensory integration/processing challenges, and supports both learners' potential and teachers' well-being, contributing to a more sustainable and positive educational experience.